Extreme Biomimetics: Designing of the First Nanostructured 3D Spongin–Atacamite Composite and its Application. Issue 30 (3rd June 2021) - Tsurkan, Dmitry; Simon, Paul; Schimpf, Christian; Motylenko, Mykhaylo; Rafaja, David; Roth, Friedrich; Inosov, Dmytro S.; Makarova, Anna A.; Stepniak, Izabela; Petrenko, Iaroslav; Springer, Armin; Langer, Enrico; et al.
Abstract: The design of new composite materials using extreme biomimetics is of crucial importance for bioinspired materials science. Further progress in research and application of these new materials is impossible without understanding the mechanisms of formation, as well as structural features at the molecular and nano‐level. It presents a challenge to obtain a holistic understanding of the mechanisms underlying the interaction of organic and inorganic phases under conditions of harsh chemical reactions for biopolymers. Yet, an understanding of these mechanisms can lead to the development of unusual—but functional—hybrid materials. In this work, a key way of designing centimeter‐scale macroporous 3D composites, using renewable marine biopolymer spongin and a model industrial solution that simulates the highly toxic copper‐containing waste generated in the production of printed circuit boards worldwide, is proposed. A new spongin–atacamite composite material is developed and its structure is confirmed using neutron diffraction, X‐ray diffraction, high‐resolution transmission electron microscopy/selected‐area electron diffraction, X‐ray photoelectron spectroscopy, near‐edge X‐ray absorption fine structure spectroscopy, and electron paramagnetic resonance spectroscopy. The formation mechanism for this material is also proposed. This study provides experimental evidence suggesting multifunctional applicability of the designed composite in the development of 3D constructed sensors, catalysts, and antibacterial filter systems. Abstract : An extreme biomimetics key way for designing of multifunctional macroporous 3D atacamite‐based composites using the renewable biopolymer spongin is proposed. Neutron diffraction, X‐ray diffraction, selected‐area electron diffraction, X‐ray photoelectron spectroscopy, electron paramagnetic resonance, and near‐edge X‐ray absorption fine structure spectroscopy provide insights, which help to understand a mechanism for its formation from a model solution that simulates the highly toxic copper‐containing waste generated in the production of printed circuit boards worldwide.